INFLUENCE OF EATING BEHAVIOR ON THE PREVALENCE OF DISEASES OF THE CIRCULATORY SYSTEM AND THEIR RISK FACTORS - Alakbarov, M.M.; Naghiyeva, R.G.; Jabbarova, N.R.; Badalova, A.O.; Taghiyeva, A.A.; Mehdiyeva, A.F.; Jafarova, A.H. (World of Medicine and Biology, 2025)
Using a sociological research program to study the characteristics of the eating behavior of the population and their impact on the prevalence of diseases of the circulatory system, as well as an adapted version of the Dutch Eating Behavior Questionnaire, a study was conducted among 620 people. It was found that 32.9 % of the population had restrained eating disorders, 30.3±1.8 % had emotional eating disorders, 18.6±1.6 % had external eating disorders, and 48.6 % had adherence to certain eating behavior stereotypes. Various factors affecting the types and degrees of eating disorder and the prevalence of eating behavior stereotypes have been identified, and the influence of each of them on the development of circulatory system pathologies and the activation of risk factors has been determined.